2005
DOI: 10.1210/er.2005-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apoptosis in the Regulation of Trophoblast Survival and Differentiation during Pregnancy

Abstract: Apoptosis is important for normal placental development, but it may also be involved in the pathophysiology of pregnancy-related diseases. Normal placental development is dependent upon the differentiation and invasion of the trophoblast, the main cellular component of the placenta. Trophoblast apoptosis increases in normal placentas as gestation proceeds, and a greater incidence of trophoblast apoptosis has been observed in pregnancies complicated by preeclampsia or intrauterine growth retardation (IUGR). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
172
0
32

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(207 citation statements)
references
References 195 publications
3
172
0
32
Order By: Relevance
“…XIAP and several other IAP family members have been shown to be expressed by the trophoblast throughout normal pregnancy (3, 38 -40) and are thought to play a critical role in regulating trophoblast cell survival (41). The function of the IAP family is inhibited by a group of proteins that includes Smac/DIABLO, OMI/HtrA2, and XAF1, albeit by different mechanisms (9, 19 -23).…”
Section: Discussionmentioning
confidence: 99%
“…XIAP and several other IAP family members have been shown to be expressed by the trophoblast throughout normal pregnancy (3, 38 -40) and are thought to play a critical role in regulating trophoblast cell survival (41). The function of the IAP family is inhibited by a group of proteins that includes Smac/DIABLO, OMI/HtrA2, and XAF1, albeit by different mechanisms (9, 19 -23).…”
Section: Discussionmentioning
confidence: 99%
“…A maturação placentária é mediada pela apoptose das células das criptas do epitélio materno e ocorre durante toda a gestação na renovação normal (Boos et al 2003), aumentando no terço final. Straszewski-Chavez et al (2005) avaliaram placentas humanas e demonstraram maior apoptose nos sítios de invasão do trofoblasto no epitélio materno, sugerindo que este processo facilite a invasão do trofoblasto e a remodelação dos vilos endometriais.…”
Section: Discussionunclassified
“…Liu et al (2003) relataram aumento da marcação para caspase-3 no sincicio e citotrofoblasto ao decorrer da gestação. Padrões crescentes de apoptose na placenta humana durante a gestação também foi observada e relacionada à constante renovação e remodelação tecidual como um processo natural por Straszewski-Chavez et al (2005).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Apoptosis and the factors involved in the regulation are associated with almost all stages of development and trophoblast differentiation. 8 One of the factors that can lead to the increased apoptosis of trophoblast during pregnancy is intrauterine infection. 9 The exact mechanism of infection resulted the progression of this disorder is not clearly understood, but recent studies suggested that bacterial products have a direct effect on the trophoblast.…”
Section: 2mentioning
confidence: 99%